Familiar Tonal Context Improves Accuracy of Pitch Interval Perception - Graves, Jackson E.; Oxenham, Andrew J. (Frontiers in Psychology, 2017)
A fundamental feature of everyday music perception is sensitivity to familiar tonal structures such as musical keys. Many studies have suggested that a tonal context can enhance the perception and representation of pitch. Most of these studies have measured response time, which may reflect expectancy as opposed to perceptual accuracy. We instead used a performance-based measure, comparing participants’ ability to discriminate between a “small, in-tune” interval and a “large, mistuned” interval in conditions that involved familiar tonal relations (diatonic, or major, scale notes), unfamiliar tonal relations (whole-tone or mistuned-diatonic scale notes), repetition of a single pitch, or no tonal context. The context was established with a brief sequence of tones in Experiment 1 (melodic context), and a cadence-like two-chord progression in Experiment 2 (harmonic context). In both experiments, performance significantly differed across the context conditions, with a diatonic context providing a significant advantage over no context; however, no correlation with years of musical training was observed. The diatonic tonal context also provided an advantage over the whole-tone scale context condition in Experiment 1 (melodic context), and over the mistuned scale or repetition context conditions in Experiment 2 (harmonic context). However, the relatively small benefit to performance suggests that the main advantage of tonal context may be priming of expected stimuli, rather than enhanced accuracy of pitch interval representation.